To solve the system using substitution, we'll first solve one of the equations for one variable and substitute it into the other equation.
From the first equation, we have y = 2 + 3x.
Substituting y = 2 + 3x into the second equation, we get:
4x - 3(2 + 3x) = -16
4x - 6 - 9x = -16
-5x - 6 = -16
-5x = -10
x = 2
Substituting this value of x back into y = 2 + 3x, we get:
y = 2 + 3(2)
y = 2 + 6
y = 8
Therefore, the solution to the system of equations is (2, 8).
Solve the system of two equations using substitution.%0D%0Ay=2+3x%0D%0A4x−3y=−16(1 point)%0D%0AResponses%0D%0A%0D%0A(−2, 4)%0D%0A left parenthesis negative 2 comma 4 right parenthesis%0D%0A%0D%0A(2, 10)%0D%0A left parenthesis 2 comma 10 right parenthesis%0D%0A%0D%0A(−2, −4)%0D%0A left parenthesis negative 2 comma negative 4 right parenthesis%0D%0A%0D%0A(2, 8)
1 answer